Komitmen Pemerintah Daerah Dalam Pengelolaan Anggaran Pendapatan Dan Belanja Daerah (Studi Pada Pemerintah Kota Bima) - Yaqin, Uun Ainul; Herwanti, Titik; Akram, Akram (E-Jurnal Akuntansi; Vol 25 No 3 (2018), 2018)
This is qualitative research and the approach is case study. This research is to know the Bima Municipality APBD’s Allocated on 2012-2016.The analysis uses the direction of regional financial management policies based on Permandagri No.59 2017. The data collection was conducted by interview through using purposive sampling. The result shows the local government commitment in financial management both from local income and expenditure is still less, it can be seen from the dependence of the regional government on the transfer funds from central government is low and the allocation of regional expenditure is not efficient and ineffective not oriented on performance-based budget. In finding suggested for improvement recommendation such as allocating the budget that emphasize on increasing the local income from PAD and expenditure allocation that is efficient and effective, for the future the budget allocation can success based on the goal and can increase the society’s welfare and give contribution on real local income improvement. Keywords : F inancial M anagement , I ncome ,E xpenditure, E fficient and effectiv e